Stres Imobilisasi Kronik Mengganggu Memori Spasial Mencit Putih (Mus musculus) Galur Swiss Webster Jantan - Desby Juananda; Riezky Valentina Astari (ANATOMICA MEDICAL JOURNAL | AMJ, 2018)
Long-term exposure to stress may induce structural and functional alterations in the brain and particularly in hippocampus. Several studies have shown that the hippocampus plays an important role in spatial learning and memory. Certain animals can perceive stressors differently depend on stress durations and paradigms. We have designed an investigation to compare the effect of different chronic stress durations, using immobilization tubes, on mice spatial memory ability. Twenty young-adult (10-12 weeks old; 25-35 g) male Swiss Webster mice were randomly assigned into four groups: control (non-stressed) group and groups were exposed to immobilization stress 2 hours/daily (09.00-11.00 am) for 14, 21 and 28 days, respectively. Spatial memory ability was tested by using Morris Water Maze. Data were analyzed with one-way ANOVA (p<0.05). We found that mean escape latency (s) for control, 2h/14 days, 2h/21 days and 2h/28 days groups were 8.49 ± 0.91, 12.40 ± 3.76, 13.73 ± 4.09, and 41.62 ± 21.84, respectively (p<0.05). Post-hoc analysis showed a statistical difference between control and stressed groups (p<0.05), but there was no statistical difference between 2h/21 days and 2h/14 days group (p>0.05). In conclusion, this study showed that chronic immobilization stress had been proven to impair spatial memory ability in mice. Specifically, our findings support the use of 2h/28 days chronic immobilization paradigm as an efficient method to induce spatial memory deficits in mice. Keywords: immobilization stress, Morris Water Maze, spatial memory